REVITALISASI PENDIDIKAN KEJURUAN AGRIBISNIS PENGOLAHAN HASIL PERTANIAN MELALUI PENGEMBANGAN KURIKULUM BERBASIS INDUSTRI, TEACHING FACTORY DAN SERTIFIKASI KOMPETENSI - ., Sahirman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): Juni, 2019)
Indonesia entered  the ASEAN Economic Community (MEA) as of December 31, 2015. In essence the purpose of the establishment of the MEA is to improve the stability of the economy in the ASEAN region, and is expected to overcome the problems in the economic field among ASEAN countries. The consequences of the MEA deal are the free flow of goods and services, free flow of capital and investment, and free flow of skilled labor for ASEAN countries. Free flow of labor is seen as a threat as well as an opportunity for the state of Indonesia. Therefore the Government of Indonesia through the Education and Culture Ministry, especially the Directorate of Vocational Secondary Education implemented a policy strategy of SMK revitalization. The aim of Vocational Revitalization is to realize the school Link and Match with the Business / Industry World (DuDi) thus eliminating the gap between  vocational education and DuDi's needs. Three important activities in the implementation strategy of SMK revitalization are the development of industry-based curriculum, teaching factory, and graduate competency certification. Activity is applied to a variety of expertise programs one of which is a program Agribusiness of Agricultural Product Processing (Agroindustry). Keywords : MEA, free flow of labor, teaching factory, competency certification.